2009
DOI: 10.1017/s1481803500011222
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a nurse practitioner on patient care in a Canadian emergency department

Abstract: Objective: Our objective was to determine whether the addition of a broad-scope nurse practitioner (NP) would improve emergency department (ED) wait times, ED lengths of stay (LOS) and left-without-treatment (LWOT) rates. We hypothesized that the addition of a broad-scope NP during weekday ED shifts would result in shorter patient wait times, reduced LOS and fewer patients leaving the ED without treatment. Methods: This prospective observational study was conducted in a busy urban free-standing community ED. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 20 publications
(24 reference statements)
2
54
0
Order By: Relevance
“…In addition to satisfaction with care, length of stay time on the obstetric triage unit was significantly lower when the CNM‐managed model of care was implemented. These findings are consistent with the studies of emergency department triage settings, which demonstrated reduced length of stay times when care was managed by a nurse practitioner . A dedicated provider in an obstetric triage unit can see women in a more timely and efficient manner.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition to satisfaction with care, length of stay time on the obstetric triage unit was significantly lower when the CNM‐managed model of care was implemented. These findings are consistent with the studies of emergency department triage settings, which demonstrated reduced length of stay times when care was managed by a nurse practitioner . A dedicated provider in an obstetric triage unit can see women in a more timely and efficient manner.…”
Section: Discussionsupporting
confidence: 87%
“…Consequently, there is a need to consider new models for managing obstetric triage units. Recent research suggests that employing nurse practitioners in an emergency setting reduces patient waiting times, improves patient satisfaction, and is cost‐effective . Therefore, using certified nurse‐midwives/certified midwives (CNMs/CMs) and registered nurses (RNs) to manage an obstetric triage unit in collaboration with obstetrician‐gynecologists has the potential to increase satisfaction with care and reduce the length of stay on the unit.…”
Section: Introductionmentioning
confidence: 99%
“…Patients treated by the midlevel provider group had a 64-minute reduction in LOS compared with patients seen by attendings. Steiner and colleagues 33 found that their midlevel providers expedited the care of low acuity patients; however, they found no reduction in overall LOS. At MMC, our midlevel providers work in a separate section of the ED that is typically populated with lower-acuity patients.…”
Section: Discussionmentioning
confidence: 97%
“…Accumulating evidence supports the beneficial contribution of nurse practitioners in acute care settings. Nurse practitioners' care was associated with decreased waiting time in emergency department [26], reduced length of hospital stay and costs [27] and increased satisfaction with care [28]. A few quantitative and qualitative studies were conducted to explore nurse practitioners' practices that may account for positive outcomes observed.…”
Section: Responsive Carementioning
confidence: 99%